Additive-manufactured nickel-based high-temperature alloy component and preparation method thereof
By optimizing chemical composition and process flow in nickel-based high-temperature alloys, including vacuum induction smelting and selective laser melting, combined with solid solution heat treatment and aging heat treatment, the problem of low high-temperature durability of high-temperature alloy components in additive manufacturing technology is solved, and the problem of low high-temperature durability of high-temperature alloy components is achieved. The nickel-based high-temperature alloy member has stability for a long time of use above 900°C.
Patent Information
- Application Number
- CN202411251005.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The high-temperature alloy components prepared by existing additive manufacturing technology have problems with low high-temperature long-lasting performance during long-term use of above 900°C, which cannot meet the needs of aerospace and aerospace power systems.
The chemical composition of a nickel-based high-temperature alloy is adopted, including C: 0.14 wt% to 0.2 wt%, Co: 21 wt% to 23 wt%, B: 0.09 wt% to 0.13 wt%, Zr: 0.015 wt% to 0.025 wt%, and passing through vacuum Induction smelting and selection laser melting processes prepare components, and solid solution heat treatment and aging heat treatment are carried out to ensure that the average grain size of the components reaches more than 300μm, the atomic ratio of C/B is ≥1.2, and the grain boundary strength is enhanced.
It significantly improves the high-temperature and durability of nickel-based high-temperature alloy components, meets the needs of long-term use above 900℃, and has a long-lasting life of more than 35 hours, ensuring the stability and mechanical properties of the components at high temperatures.
Smart Images

Figure CN119120993A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-temperature alloys, and in particular, relates to an additively manufactured nickel-based high-temperature alloy component and a preparation method thereof. Background Art
[0002] High-temperature alloys have excellent mechanical properties and good oxidation resistance and corrosion resistance. They are key materials for the preparation of hot-end components of aerospace and aviation power systems. With the continuous development of the aerospace and aviation industries, the design requirements of core components have gradually increased, and more complex internal flow channels and thin-walled structures have appeared inside the parts. Traditional casting, forging and welding processes can no longer meet the design requirements. Selective laser melting (SLM) technology is a rapid additive manufacturing technology that can melt metal powder layer by layer to ultimately achieve mold-free, high-density, near-net-shape metal parts. Selective laser melting technology has the characteristics of high forming efficiency and the ability to prepare complex structural parts. It has become the preferred solution for the preparation of complex structural parts of high-temperature alloys.
[0003] There are many types of high-temperature alloys that have been used in hot-end components, but most of them are developed for traditional casting and forging processes. Since the forming process of additive manufacturing technologies such as SLM is completely different from that of traditional processes, when SLM is used to replace traditional processes to prepare high-temperature alloy components, there is a problem of low high-temperature durability, which cannot meet the needs of long-term use above 900°C. The durability is mostly only a few hours, which seriously restricts the application of additive manufacturing technology in the preparation of high-temperature alloy components.
[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defect of low high-temperature durability of high-temperature alloy components prepared by additive manufacturing technologies such as SLM in the prior art, and to provide a nickel-based high-temperature alloy component manufactured by additive manufacturing and a preparation method thereof, wherein the high-temperature alloy component has significantly improved high-temperature durability.
[0006] In order to achieve the above-mentioned objectives, in a first aspect, the present invention provides an additively manufactured nickel-based high-temperature alloy component, whose chemical composition includes: C: 0.14wt%~0.2wt%, Co: 21wt%~23wt%, B: 0.09wt%~0.13wt%, Zr: 0.015wt%~0.025wt%, 0.25wt%≤C+B≤0.32wt%, and the atomic ratio of C / B is ≥1.2; the average grain size of the component is above 300μm, and the durability of the component is above 35h, and the durability is obtained by testing at 900℃ and 172MPa.
[0007] In some preferred embodiments, the chemical composition further comprises: Co+B≥22.5wt%.
[0008] Preferably, the chemical composition includes: B: 0.1wt% to 0.12wt%, Zr: 0.015wt% to 0.023wt%.
[0009] In some preferred embodiments, the chemical composition also includes: Cr: 21.5wt% ~ 23.5wt%, W: 1.7wt% ~ 2.3wt%, Al: 1.0wt% ~ 1.6wt%, Ti: 2.5wt% ~ 2.7wt%, Nb: 0.6wt% ~ 1.0wt%, Ta: 0.7wt% ~ 1.3wt%, the remainder is Ni and unavoidable impurity elements, 44wt% ≤ Cr + Co ≤ 46wt%.
[0010] Preferably, the chemical composition further includes: 4wt%≤Al+Ti≤4.3wt%.
[0011] In some preferred embodiments, the density of the nickel-based high-temperature alloy component is ≥99%.
[0012] In a second aspect, the present invention provides a method for preparing the nickel-based high-temperature alloy component according to the first aspect, comprising the following steps: obtaining a master alloy ingot based on vacuum induction melting and casting;
[0013] preparing the master alloy ingot into alloy powder;
[0014] The alloy powder is prepared into a component preform based on a selective laser melting process, and the component preform is subjected to a solution heat treatment and an aging heat treatment to obtain the nickel-based high-temperature alloy component. The conditions of the solution heat treatment include: a heating rate of 3°C / min to 7°C / min, a holding temperature of 1250°C to 1280°C, and a holding time of 2h to 3h.
[0015] In some preferred embodiments, the heating rate of the solution heat treatment is 3°C / min to 5°C / min.
[0016] In some preferred embodiments, the conditions of the solution heat treatment also include: furnace cooling; the conditions of the aging heat treatment include: heating rate of 4°C / min to 7°C / min, holding temperature of 700°C to 900°C, holding time of 8h to 10h, and air cooling.
[0017] In some preferred embodiments, the alloy powder has a particle size distribution of 15 μm to 45 μm.
[0018] The chemical composition of the additively manufactured nickel-based high-temperature alloy component of the present invention includes a C content of 0.14wt% to 0.2wt%, which promotes the formation of dispersed carbides at the grain boundaries, a Co content of 21wt% to 23wt%, which can significantly reduce the stacking fault energy of the alloy matrix, is conducive to the formation of twins, and the dislocation consumes a lot of energy in the movement of the crystal, which can delay the aggregation of dislocations at the grain boundaries, a B content of 0.09wt% to 0.13wt%, which promotes the coordinated deformation of the grain boundaries during the additive manufacturing process, and a Zr content of 0.015wt% to 0.025wt%, which can purify the grain boundaries. By respectively setting the C content, the Co content, the B content, and the Zr content in the above ranges, based on boronization The material can absorb harmful elements such as S and P to significantly improve the grain boundary strength, 0.25wt%≤C+B≤0.32wt%, and the atomic ratio of C / B≥1.2, which can ensure that the alloy has good grain boundary strength without deteriorating the additive manufacturing process performance of the alloy. The average grain size of the component is above 300μm, which can reduce the grain boundary ratio in the alloy structure. On the one hand, it has significantly improved grain boundary strength. On the other hand, the low grain boundary ratio in the alloy structure can improve the high-temperature durability of additively manufactured nickel-based high-temperature alloy components and meet the needs of long-term use above 900℃. The durability life of the component tested at 900℃ and 172MPa is more than 35h. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 This is the grain structure and grain size distribution diagram of the nickel-based high-temperature alloy component of Example 1.
[0021] Figure 2 This is the metallographic structure diagram of the nickel-based high-temperature alloy component of Example 1. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The inventors of the present invention have found through research that in the prior art, high-temperature alloy components manufactured using additive manufacturing technologies such as SLM have low high-temperature durability.
[0024] In this regard, in a first aspect, the present invention provides an additively manufactured nickel-based high-temperature alloy component, whose chemical composition includes: C: 0.14wt%~0.2wt%, Co: 21wt%~23wt%, B: 0.09wt%~0.13wt%, Zr: 0.015wt%~0.025wt%, 0.25wt%≤C+B≤0.32wt%, and the atomic ratio of C / B is ≥1.2; the average grain size of the component is above 300μm, and the durability of the component is above 35h, and the durability is obtained by testing at 900℃ and 172MPa.
[0025] The chemical composition of the nickel-based high-temperature alloy component manufactured by the additive manufacturing of the present invention includes C: 0.14wt% to 0.2wt%, Co: 21wt% to 23wt%, B: 0.09wt% to 0.13wt%, Zr: 0.015wt% to 0.025wt%, 0.25wt%≤C+B≤0.32wt%, and the atomic ratio of C / B is ≥1.2. The composition of the alloy ingot and alloy powder used for additive manufacturing is also basically within the above range, and the C content is 0.14wt% to The content of B is 0.09wt% to 0.13wt%, which can increase the plasticity of the alloy and promote the coordinated deformation of the grain boundaries during additive manufacturing. The content of Co is 21wt% to 23wt%, which can reduce the stacking fault energy of the alloy matrix and is conducive to the formation of twins. The dislocation consumes a lot of energy in the movement of the crystal, which can delay the aggregation of dislocations at the grain boundaries, increase the fracture time of the alloy, and improve the alloy's Temperature performance, improve alloy forming performance and organizational stability, Zr content is 0.015wt% ~ 0.025wt%, can purify grain boundaries, improve alloy plasticity, through C content, Co content, B content, Zr content are respectively in the above range, based on the boride can absorb harmful elements such as S, P and significantly improve the grain boundary strength, 0.25wt% ≤ C + B ≤ 0.32wt%, C / B atomic ratio ≥ 1.2, can ensure that the alloy has good grain boundary strength while not deteriorating the additive manufacturing process performance of the alloy, the component does not crack, the average grain size of the component is 300μm or more, can reduce the grain boundary ratio in the alloy organization, on the one hand has significantly improved grain boundary strength, on the other hand the grain boundary ratio in the alloy organization is low, can improve the high temperature endurance performance of the additively manufactured nickel-based high temperature alloy components, meet the needs of long-term use above 900 ℃, the endurance life of the component tested at 900 ℃, 172MPa is more than 35h, the life of the component is evaluated by whether the component breaks and fails. The high-temperature durability of the nickel-based high-temperature alloy component of the present invention is significantly improved, and the alloy additive manufacturing process performance is still very excellent.
[0026] The Co content of the nickel-based high-temperature alloy component of the present invention is 21wt%-23wt%, Co is completely miscible with the matrix Ni, can expand the γ phase region, and promote solid solution strengthening in the alloy. The C content is 0.14wt%-0.2wt%, which is beneficial to deoxidation during the alloy smelting process and can improve the purity of the high-temperature alloy. When the C content is higher than 0.2wt%, continuous carbides will be precipitated at the grain boundaries, which is not conducive to the mechanical properties of the alloy. When the Zr content is higher than 0.025wt%, the solidus temperature will be reduced. When the B content is higher than 0.13wt%, a large amount of borides formed are not conducive to the mechanical properties of the alloy.
[0027] The C content of the nickel-based high-temperature alloy component of the present invention can be, for example, 0.14wt%, 0.16wt%, 0.18wt% and 0.2wt%, the Co content can be, for example, 21wt%, 21.5wt%, 22wt%, 22.5wt% and 23wt%, the B content can be, for example, 0.09wt%, 0.1wt%, 0.11wt% and 0.13wt%, and the Zr content can be, for example, 0.015wt%, 0.018wt%, 0.019wt%, 0.10wt%, 0.110wt% and 0.12wt%. .02wt%, 0.022wt% and 0.025wt%, the content of C+B can be, for example, 0.25wt%, 0.27wt%, 0.29wt%, 0.31wt% and 0.32wt%, the atomic ratio of C / B can be, for example, 1.2, 1.4, 1.6, 1.8 and 2, and the average grain size of the component can be, for example, 300μm, 350μm, 400μm, 450μm, 500μm, 550μm, 600μm.
[0028] In some preferred embodiments, the chemical composition further includes: Co+B≥22.5wt%. Co is beneficial to reducing stacking fault energy and delaying the aggregation of dislocations at grain boundaries, and B can promote coordinated deformation of grain boundaries during additive manufacturing. In this preferred embodiment, Co+B≥22.5wt%, which is more beneficial to reducing or slowing down the sliding of grain boundaries at high temperatures, improving grain boundary strength, and improving the high temperature durability of the alloy. The content of Co+B can be, for example, 22.5wt%, 22.6wt%, 22.7wt%, 22.8wt%, 22.9wt%, 23wt% and 23.1wt%.
[0029] Preferably, the chemical composition includes: B: 0.1wt% to 0.12wt%, Zr: 0.015wt% to 0.023wt%. In this preferred embodiment, the B content and Zr content are respectively within the above ranges, which is more conducive to improving the grain boundary strength, improving the high temperature durability of the nickel-based high temperature alloy component, and improving the durability life.
[0030] In some preferred embodiments, the chemical composition also includes: Cr: 21.5wt% ~ 23.5wt%, W: 1.7wt% ~ 2.3wt%, Al: 1.0wt% ~ 1.6wt%, Ti: 2.5wt% ~ 2.7wt%, Nb: 0.6wt% ~ 1.0wt%, Ta: 0.7wt% ~ 1.3wt%, the remainder is Ni and unavoidable impurity elements, 44wt% ≤ Cr + Co ≤ 46wt%.
[0031] Under this preferred embodiment, the Cr element content is not less than 21.5wt%, which is more conducive to promoting the solid solution strengthening of the nickel-based high-temperature alloy, forming an oxide layer on the metal surface to improve the oxidation resistance of the alloy, the Cr element content is not higher than 23.5wt%, which is more conducive to preventing the precipitation of harmful secondary phases, avoiding component cracking, and improving the high-temperature mechanical properties of the alloy, 44wt%≤Cr+Co≤46wt%, which is more conducive to ensuring the additive manufacturing process performance of the alloy, the Cr+Co content is not less than 44wt%, which is more conducive to preventing component cracking, and the Cr+Co content is not higher than 46wt%, which is more conducive to controlling the formation of TCP phase; the W element content is not less than 1.7wt%, W is dissolved in both the γ matrix and the γ′ phase, which is more conducive to increasing the dissolution temperature and stability of the γ′ phase, increasing the volume fraction of the γ′ phase, improving the solid solution strengthening effect, and controlling the coarsening rate of the γ′ phase. The W element content is not higher than 2.3wt%, which is more conducive to controlling the formation of the TCP phase; the Al element content is not less than 1.0wt%, which is more conducive to The content of Ti element is not less than 2.5wt%, which is more conducive to improving the dissolution temperature and stability of γ′ phase, improving the volume fraction of γ′ phase, forming a dense oxide film at high temperature, and improving the oxidation resistance of the alloy. The content of Ti element is not more than 2.7wt%, which is more conducive to controlling the decrease of solidus temperature, controlling the coarsening rate of γ′ phase, and controlling the formation of low-melting-point γ / γ′ eutectic between dendrites. The content of Nb element is not less than 0.6wt%, which is more conducive to improving the dissolution temperature of γ′ phase and enhancing the high-temperature mechanical properties of the alloy. The content of Nb element is not less than 1.0wt%, which is more conducive to controlling the precipitation of TCP harmful phase. Ta element is easy to segregate in γ′ phase. The content of Ta element is not less than 0.7wt%, which is more conducive to improving the dissolution temperature and stability of γ′ phase and enhancing the high-temperature mechanical properties of the alloy. The content of Ta element is not more than 1.3wt%, which is more conducive to preventing the precipitation of harmful secondary phase and reducing the cracking tendency of components.
[0032] The Cr content of the nickel-based high-temperature alloy component of the present invention can be, for example, 21.5wt%, 22wt%, 22.5wt%, 23wt% and 23.5wt%, the W content can be, for example, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt and 2.3wt%, the Al content can be, for example, 1.0wt%, 1.2wt%, 1.4wt% and 1.6wt%, the Ti content can be, for example, 2.5wt%, 2.55wt%, 2.6wt%, 2.65wt% and 2.7wt%, the Nb content can be, for example, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% and 1wt%, the Ta content can be, for example, 0.7wt%, 0.9wt%, 1.1wt% and 1.3wt%, and the Cr+Co content can be, for example, 44wt%, 44.5wt%, 45wt%, 45.5wt% and 46wt%.
[0033] Preferably, the chemical composition further comprises: 4wt%≤Al+Ti≤4.3wt%. Under this preferred solution, it is more conducive for the nickel-based high-temperature alloy component to maintain a higher strength.
[0034] In some preferred embodiments, the density of the nickel-based high-temperature alloy component is ≥99%.
[0035] In a second aspect, the present invention provides a method for preparing the nickel-based high-temperature alloy component according to the first aspect, comprising the following steps:
[0036] Based on vacuum induction melting and casting, a master alloy ingot is obtained;
[0037] preparing the master alloy ingot into alloy powder;
[0038] The alloy powder is prepared into a component preform based on a selective laser melting process, and the component preform is subjected to a solution heat treatment and an aging heat treatment to obtain the nickel-based high-temperature alloy component. The conditions of the solution heat treatment include: a heating rate of 3°C / min to 7°C / min, a holding temperature of 1250°C to 1280°C, and a holding time of 2h to 3h.
[0039] The preparation method of the nickel-based high-temperature alloy component of the present invention can control the chemical composition of the master alloy ingot, alloy powder and nickel-based high-temperature alloy component by controlling the proportion of ingredients in vacuum induction melting and casting. After the component preform is prepared by the selective laser melting process, a solid solution heat treatment is performed, and the heating rate of the solid solution heat treatment is 3°C / min to 7°C / min, and the heating rate is not higher than 7°C / min, which is more conducive to ensuring that the average grain size of the component is more than 300μm. The holding temperature of the solid solution heat treatment is not less than 1250°C, which is more conducive to fully recrystallizing and growing the grains, ensuring that the average grain size reaches more than 300μm. After the solid solution heat treatment, an aging heat treatment is performed, which is more conducive to the precipitation of r' phase and improving the strength of the nickel-based high-temperature alloy component. The process of preparing the alloy powder of the present invention is preferably carried out by vacuum gas atomization or plasma rotating electrode powder making.
[0040] The heating rate of the solution heat treatment can be, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min and 7°C / min, the holding temperature can be, for example, 1250°C, 1260°C, 1270°C and 1280°C, and the holding time can be, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h and 3h.
[0041] In some preferred embodiments, the heating rate of the solution heat treatment is 3°C / min to 5°C / min. This preferred solution is more conducive to increasing the grain size, reducing the grain boundary ratio, and improving high temperature durability.
[0042] In some preferred embodiments, the conditions of the solution heat treatment also include: furnace cooling; the conditions of the aging heat treatment include: heating rate of 4℃ / min~7℃ / min, holding temperature of 700℃~900℃, holding time of 8h~10h, air cooling. Under this preferred scheme, the heating rate of the aging heat treatment is 4℃ / min~7℃ / min, the holding temperature is 700℃~900℃, and the holding time is 8h~10h, which is more conducive to the precipitation of r' phase and improves the strength of nickel-based high-temperature alloy components.
[0043] In some preferred embodiments, the particle size distribution of the alloy powder is 15 μm to 45 μm. In this preferred embodiment, the particle size distribution of the alloy powder is 15 μm to 45 μm, which is more conducive to improving the mechanical properties of nickel-based high-temperature alloy components. The alloy powder of the present invention is preferably a spherical alloy powder.
[0044] In some preferred embodiments, the laser power of the selective laser melting process is 200W to 400W, the laser scanning speed is 500mm / s to 700mm / s, the spot diameter is 80μm to 120μm, the laser scanning interval is 70μm to 90μm, and the powder thickness is 20μm to 40μm, which is more conducive to the high temperature durability of nickel-based high temperature alloy components.
[0045] The present invention is further described in detail below with reference to specific embodiments.
[0046] Example 1
[0047] A method for preparing a nickel-based high-temperature alloy component, the preparation steps are as follows:
[0048] Step 1: After the ingredients are proportioned, vacuum induction melting and casting are performed to obtain a master alloy ingot;
[0049] Step 2: The master alloy ingot of step 1 is subjected to vacuum gas atomization to obtain nickel-based high-temperature alloy powder with a particle size of 15 to 45 μm;
[0050] Step three: prepare a nickel-based high-temperature alloy component preform by a selective laser melting process on the nickel-based high-temperature alloy powder of step two; the process parameters of the selective laser melting process are: laser power of 300W, laser scanning speed of 600mm / s, spot diameter of 100μm, laser scanning spacing of 80μm, powder thickness of 30μm, and the nickel-based high-temperature alloy component preform is successively subjected to solution heat treatment and aging heat treatment to obtain a nickel-based high-temperature alloy component, the heating rate of the solution heat treatment is 5℃ / min, the holding temperature is 1270℃, the holding time is 2h, and furnace cooling is performed after holding, the heating rate of the aging heat treatment is 5℃ / min, the holding temperature is 800℃, the holding time is 8h, and air cooling is performed after holding.
[0051] The composition of the nickel-based high-temperature alloy component prepared in this embodiment is C: 0.2wt%, Cr: 22.4wt%, Co: 23wt%, W: 2.1wt%, Al: 1.58wt%, Ti: 2.68wt%, Nb: 0.98wt%, B: 0.12wt%, Ta: 1.2wt%, Zr: 0.023wt%, and the remainder is Ni and impurity elements, C+B is 0.32wt%, the atomic ratio of C / B is 1.5, Co+B is 23.12wt%, Cr+Co is 45.4wt%, and Al+Ti is 4.26wt%.
[0052] Example 2
[0053] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.18wt%, Cr: 22.3wt%, Co: 22.5wt%, W: 2.2wt%, Al: 1.56wt%, Ti: 2.66wt%, Nb: 0.96wt%, B: 0.13wt%, Ta: 1.19wt%, Zr: 0.025wt%, and the balance is Ni and unavoidable impurities, C+B is 0.31wt%, the atomic ratio of C / B is 1.25, Co+B is 22.63wt%, Cr+Co is 44.8wt%, and Al+Ti is 4.22wt%.
[0054] Example 3
[0055] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.2wt%, Cr: 22.5wt%, Co: 22wt%, W: 2.3wt%, Al: 1.58wt%, Ti: 2.67wt%, Nb: 0.98wt%, B: 0.12wt%, Ta: 1.2wt%, Zr: 0.025wt%, and the balance is Ni and unavoidable impurities, C+B is 0.32wt%, the atomic ratio of C / B is 1.5, Co+B is 22.12wt%, Cr+Co is 44.5wt%, and Al+Ti is 4.25wt%.
[0056] Example 4
[0057] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.2wt%, Cr: 22.4wt%, Co: 22.8wt%, W: 2.3wt%, Al: 2.6wt%, Ti: 2.7wt%, Nb: 0.96wt%, B: 0.12wt%, Ta: 1.2wt%, Zr: 0.024wt%, and the balance is Ni and unavoidable impurities, C+B is 0.32wt%, the atomic ratio of C / B is 1.5, Co+B is 22.92wt%, Cr+Co is 45.2wt%, and Al+Ti is 5.3wt%.
[0058] Example 5
[0059] The preparation method is carried out in accordance with Example 1, except that in step 3, the heating rate of the solution heat treatment is 6°C / min.
[0060] Comparative Example 1
[0061] The preparation method is carried out in accordance with Example 1, except that in step 3, the heating rate of the solution heat treatment is 8°C / min.
[0062] Comparative Example 2
[0063] The preparation method is carried out in accordance with Example 1, except that in step 3, the holding temperature of the solution heat treatment is 1230°C.
[0064] Comparative Example 3
[0065] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.2wt%, Cr: 22.8wt%, Co: 22.6wt%, W: 2.2wt%, Al: 1.6wt%, Ti: 2.7wt%, Nb: 1.0wt%, B: 0.05wt%, Ta: 1.2wt%, Zr: 0.022wt%, and the balance is Ni and unavoidable impurities, C+B is 0.25wt%, the atomic ratio of C / B is 3.6, Co+B is 22.65wt%, Cr+Co is 45.4wt%, and Al+Ti is 4.3wt%.
[0066] Comparative Example 4
[0067] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.2wt%, Cr: 23.4wt%, Co: 20.5wt%, W: 2.2wt%, Al: 1.6wt%, Ti: 2.6wt%, Nb: 1.0wt%, B: 0.11wt%, Ta: 1.3wt%, Zr: 0.022wt%, and the balance is Ni and unavoidable impurities, C+B is 0.31wt%, the atomic ratio of C / B is 1.64, Co+B is 20.61wt%, Cr+Co is 43.9wt%, and Al+Ti is 4.2wt%.
[0068] Comparative Example 5
[0069] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.14wt%, Cr: 23.5wt%, Co: 22.5wt%, W: 2.2wt%, Al: 1.5wt%, Ti: 2.7wt%, Nb: 1.0wt%, B: 0.1wt%, Ta: 1.3wt%, Zr: 0.022wt%, and the balance is Ni and unavoidable impurities, C+B is 0.24wt%, the atomic ratio of C / B is 1.26, Co+B is 22.6wt%, Cr+Co is 46wt%, and Al+Ti is 4.2wt%.
[0070] Comparative Example 6
[0071] The preparation method of Example 1 is followed, except that the ingredient ratio in step one is adjusted, and the composition of the prepared nickel-based high-temperature alloy component is C: 0.14wt%, Cr: 23wt%, Co: 23wt%, W: 2.3wt%, Al: 1.6wt%, Ti: 2.6wt%, Nb: 1.0wt%, B: 0.12wt%, Ta: 1.3wt%, Zr: 0.023wt%, and the balance is Ni and unavoidable impurities, C+B is 0.26wt%, the atomic ratio of C / B is 1.05, Co+B is 23.12wt%, Cr+Co is 46wt%, and Al+Ti is 4.2wt%.
[0072] The nickel-based high-temperature alloy components obtained in the above examples and comparative examples were subjected to various performance tests shown in Table 1, and the results are shown in Table 1. The endurance life was obtained by testing at 900°C and 172MPa (Metal Tensile Creep and Endurance Test Method: GB / T 2039-1997). The grain structure and grain size distribution of the nickel-based high-temperature alloy component of Example 1 are shown in Figure 1 The metallographic structure diagram of the nickel-based high-temperature alloy component of Example 1 is shown in Figure 2, nickel-based high-temperature alloy components are uniform, dense and crack-free.
[0073] Table 1
[0074]
[0075]
[0076] In the comparative examples, comparative examples 1 and 2, the average grain size of the component is 300 μm or more, which can improve the high-temperature endurance performance. In the comparative examples and comparative examples 3, the B content is 0.09 wt% to 0.13 wt%, which can improve the high-temperature endurance performance of the component. In the comparative examples and comparative examples 4, the Co content is 21 wt% to 23 wt%, which can improve the high-temperature endurance performance of the component. In the comparative examples and comparative examples 5, 0.25 wt% ≤ C + B ≤ 0.32 wt%, which can improve the high-temperature endurance performance of the component. In the comparative examples and comparative examples 6, the atomic ratio of C / B is ≥ 1.2, which can improve the high-temperature endurance performance of the component.
[0077] Comparing Example 1 and Example 2, the B content is 0.1wt%~0.12wt%, and the Zr content is 0.015wt%~0.023wt%, which is more conducive to improving the high temperature durability of the component. Comparing Example 1 and Example 3, Co+B≥22.5wt%, which is more conducive to improving the high temperature durability of the component. Comparing Example 1 and Example 4, the Al content is 1.0wt%~1.6wt%, 4wt%≤Al+Ti≤4.3wt%, which is more conducive to improving the high temperature durability of the component. Comparing Example 1 and Example 5, the heating rate of the solution heat treatment is 3℃ / min~5℃ / min, which is more conducive to increasing the grain size and improving the high temperature durability of the component.
[0078] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An additively manufactured nickel-based high-temperature alloy component, characterized in that: Its chemical composition includes: C: 0.14wt%~0.2wt%, Co: 21wt%~23wt%, B: 0.09wt%~0.13wt%, Zr: 0.015wt%~0.025wt%, 0.25wt%≤C+B≤0.32wt%, and the atomic ratio of C / B is ≥1.2; the average grain size of the component is above 300μm, and the long-lasting life of the component is above 35h, and the long-lasting life is obtained by testing at 900℃ and 172MPa.
2. The nickel-based high-temperature alloy component according to claim 1, characterized in that: The chemical composition also includes: Co+B≥22.5wt%.
3. The nickel-based high-temperature alloy component according to claim 2, characterized in that: The chemical composition includes: B: 0.1wt% to 0.12wt%, Zr: 0.015wt% to 0.023wt%.
4. The nickel-based high-temperature alloy component according to claim 1, characterized in that: The chemical composition also includes: Cr: 21.5wt%~23.5wt%, W: 1.7wt%~2.3wt%, Al: 1.0wt%~1.6wt%, Ti: 2.5wt%~2.7wt%, Nb: 0.6wt%~1.0wt%, Ta: 0.7wt%~1.3wt%, and the balance is Ni and unavoidable impurity elements, 44wt%≤Cr+Co≤46wt%.
5. The nickel-based high-temperature alloy component according to claim 4, characterized in that: The chemical composition also includes: 4wt%≤Al+Ti≤4.3wt%.
6. The nickel-based high-temperature alloy component according to claim 1, characterized in that: The density of the nickel-based high-temperature alloy component is ≥99%.
7. A method for preparing a nickel-based high-temperature alloy component according to any one of claims 1 to 6, characterized in that: The steps include: Based on vacuum induction melting and casting, a master alloy ingot is obtained; preparing the master alloy ingot into alloy powder; The alloy powder is prepared into a component preform based on a selective laser melting process, and the component preform is subjected to a solution heat treatment and an aging heat treatment to obtain the nickel-based high-temperature alloy component. The conditions of the solution heat treatment include: a heating rate of 3°C / min to 7°C / min, a holding temperature of 1250°C to 1280°C, and a holding time of 2h to 3h.
8. The preparation method according to claim 7, characterized in that: The heating rate of the solution heat treatment is 3°C / min to 5°C / min.
9. The preparation method according to claim 7, characterized in that: The conditions of the solution heat treatment also include: furnace cooling; the conditions of the aging heat treatment include: heating rate of 4°C / min to 7°C / min, holding temperature of 700°C to 900°C, holding time of 8h to 10h, and air cooling.
10. The preparation method according to claim 7, characterized in that: The particle size distribution of the alloy powder is 15 μm to 45 μm.
